Internet use and gender wage gap: Evidence from China - Xinxin Ma (Journal for Labour Market Research, 2022)
This study explores the influence of Internet use on the gender wage gap in China by using national longitudinal survey data. A fixed effects and instrumental variable method were employed to address individual heterogeneity and other endogeneity problems. The study contributes in the form of four key conclusions. First, considering the endogeneity problems, the return to Internet use is higher for men than for women, unlike the results derived using the ordinary least squares model, which indicates the opposite. The individual heterogeneity problem considerably affects the results, thus suggesting a bias in earlier studies. The results of robustness checks based on the Internet use frequency for different purposes confirm the conclusions. Second, the gender difference in return to Internet use is higher in the low-education group and older age cohorts. Third, both the components-the gender disparity in Internet access and gender difference in return to Internet use-widen the gender wage gap, with the gender difference in return to Internet use having a higher impact. Fourth, the effects of these two components on the gender wage gap vary with the educational attainment and age cohorts.
Keywords: J16; J24; J31; O33; 330; China; Gender wage gap; Internet access; Internet use; Return to Internet use